Affective-cognitive circuits in postoperative appetite reduction: an adaptive neuroimmune response to surgical stress - Sun, Yanbo; Bao, Xianrong; Cen, Yunyun; Wu, Huiyin; Sun, Feng; Fu, Lin (Frontiers in Neuroscience, 2025)
Postoperative reduction in appetite perception, conceptualized as an interplay between emotion, perception, and cognition, may lead to adverse nutritional outcomes. However, an increasing body of research suggests that it may serve as an adaptive mechanism to inhibit inflammatory responses and regulate metabolic burden. This review comprehensively summarizes the multifaceted mechanisms underlying postoperative changes in appetite perception, particularly from the perspectives of immune regulation, inflammatory suppression, and metabolic reprogramming. Special attention is paid to the affective and cognitive dimensions of appetite perception, exploring how emotion-related processing and neurocognitive feedback contribute to appetite perception suppression during recovery. Moreover, this review highlights the clinical significance of these affective-perceptual changes in postoperative nutritional management, emphasizing the need to integrate psychological, perceptual, and neuroimmune factors into patient care strategies. Ultimately, the article explores the potential role of postoperative appetite perception reduction in modulating insulin sensitivity and improving systemic metabolic health. Based on current literature, we advocate for reevaluating appetite perception dynamics during recovery to provide novel theoretical foundations and practical directions for targeted postoperative nutritional interventions.